Let f be a one-to-one (Injective) function with domain D f = { x , y , z } and range { 1 , 2 , 3 } . It is given that only one of the following 3 statement is true and the remaining statements are false:
f ( x ) f ( y ) f ( z ) = = = 1 1 2 .
Find f − 1 ( 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How can a one-one function with equinumerous domain and range be injective (into) ?
Log in to reply
I didn't say its onto function, its an one-one function. One-one function is also known as injective function. Onto function is different from injective function.
Kunal this is perfect solution.
How are you getting that f(z) = 3 and f(x) = 2.
If f − 1 ( 1 ) = x then 1 and 2 are true. But only 1 of them is true, then f − 1 ( 1 ) = x .
If f − 1 ( 1 ) = z then 3 and 2 are true. Then f − 1 ( 1 ) = z .
We can state that y = 1 ; x = 2 ; z = 3 . Then 1 and 2 are false and 3 is true.
Remark, all values in the range must be mapped to by a unique value in the domain (unique here, since f is 1-1), since otherwise, any such value that is not mapped to does not belong in the range.
Now,
Statement 1. f(x) = 1
must be false since it immediately follows that statement 2. f(y) != 1
must be true as well, but we are only allowed a single true statement.
Let us look at statement 2 next.
If statement 2 is indeed true, then it follows that either f(y) = 2 or f(y) = 3
If f(y) = 2, it immediately follows that statement 3 is true as well; again contradicting the assumption that there's only a single true statement in our collection of assertions.
If f(y) = 3, then f(x) must equal 2, since we assume statement 1. is false, as is (i.e. f(x) != 1 and therefore f(x) = 2 since that's the only value in the range set that is left [remember, f is 1-1]). But f(x) = 2 implies statement 3. f(z) != 2 is true as well, which is a contradiction yet again.
I.e., the assumption that statement 2 is true, yields a contradiction. Therefore, this assumption must be false. It follows that statement 2 is false, and f(y) = 1.
Certainly, f^{-1}(1) = y, as desired.
Can any one explain what the image in here represent (i.e., how is this related to the question)? I am really confused
Problem Loading...
Note Loading...
Set Loading...
Let's analyse each statement one by one. 1 . If f ( x ) = 1 is true Then, f ( y ) = 1 is also true.But only one statement is true. So f ( x ) = 1 is false statement. 2 . If f ( y ) = 1 is true Then, f ( x ) = 1 and f ( z ) = 2 is false. So f ( x ) = 1 and also f ( y ) = 1 so, f ( z ) = 1 . Hence, f ( z ) = 2 is also true. But only one of given statement is true. So f ( y ) = 1 is false statement. 3 . If f ( z ) = 2 is true Then, f ( x ) = 1 and f ( y ) = 1 are false. So f ( x ) = 1 and f ( y ) = 1 . Also we can conclude f ( z ) = 3 and f ( x ) = 2 . Hence , f − 1 ( 1 ) = y .